From the ovine to human rotator cuff; tenocyte as to MSC derived exosomes for tendon healing - von Stade, Devin P., author; Regan, Daniel, advisor; McGilvray, Kirk, advisor; Santangelo, Kelly, committee member; Hollinshead, Fiona, committee member (Colorado State University. Libraries, 2024)
Tendinopathies comprise one of the most widespread and economically significant diseases in developed nations. The societal value of rotator cuff tear surgical intervention alone has been estimated at greater than 3.4 billion US dollars despite frequent repair failures (30-79%). This drives great interest in adjunct therapies; however, research is complicated by a limited understanding of the underlying pathogenesis. Recent data suggests that the primary driver is cell-to-cell communication during the acute and chronic stages of rotator cuff tears. Most notably, the paracrine signaling of macrophages, which are preferentially recruited earlier and persist longer than other immune cells, may direct the structural function of injured tendons. Extracellular vesicles (EVs) are the primary contributors to the paracrine signaling responsible for many successful cell therapy studies. Investigations into mesenchymal stromal cell (MSC) derived EVs have served as a launching point toward this end, however, cell origin can dramatically change the effect of EVs on target cells. To explore the effects of exosomes as a function of cell source on tendon healing, we have developed in vitro models in human and ovine cell lines to test the effects of tissue native, tenocyte derived EVs as they compare to MSC derived EVs on key effectors of rotator cuff tears, tenocytes and macrophages. The goal of this work is to (a) describe the direct effect of EV education, as a function of cell source, MSC vs tenocyte, on macrophage gene regulation and cytokine production and tenocyte bioactivity; (b) to then assess the indirect effects of such EV educated macrophages on tenocyte bioactivity. (c) Additionally, the underlying pathogenesis of tendinopathy and the animal models of rotator cuff tears we use will be explored and further defined in the context of contemporary histologic and biomechanical methods.
Keywords: orthopedic; tendinopathy; translational; pathology; exosome; tendon